Erythropoietic inducing potential of fermented milled rice (Oryza sativa var. Sinandomeng) water in sprague dawley rats with defarasirox-induced iron deficiency anemia - Herrera, Leah Marie B., Torres, Jaira Yoshavet M., Ventura, Airene Joy P., Villahermosa, April D., Viray, Jessica A. 4 0 16; 5
ABSTRACT: This study investigated the potential of fermented rice water (FRW) as a treatment for iron deficiency anemia (IDA) in Sprague Dawley rats (SDRs). Six groups with four replicates were used. Blood samples were collected before and after induction of deferasirox (dfx) anemia and post-treatment. Red blood cell production (erythrocyte, hemoglobin, and hematocrit levels) in SDRs with IDA was compared to groups receiving distilled water and rat chow. Groups 3-6 received an 800 mg/kg once a day of Moringa oleifera leaf extract (positive control) or fermented rice water with varying fermentation times (24, 36, or 48 hours). Group 5 (48-hour FRW) showed the greatest improvement in most parameters compared to groups 3 and 4 (24 and 36-hour FRW), which also exhibited increases in red blood cell counts and hemoglobin levels compared to the post-anemia state. Statistical analysis revealed no significant difference in efficacy between fermentation durations (p > 0.05), suggesting that 24-hour FRW preparation is sufficient to induce erythropoietic activity. Furthermore, t-test analysis of the after treatment showed no significant difference (p > 0.05) between group 3 (24-hour FRW) and 6 (positive control) suggesting potential erythropoietic activity. Additionally, a different t-test analysis confirmed a significant difference (p < 0.05) between the Group 2 (negative control) and 3 (24-hour FRW). These findings imply that fermented milled rice water may promote erythropoiesis and enhance red blood cell characteristics in SDRs with dfx-induced IDA, warranting further research to optimize treatment and explore other influencing factors.
Undergraduate Thesis: (BS Biology major in Medical Biology) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2